Effects of an 8-week Baduanjin intervention combined with low-carbohydrates diet among overweight people who struggle with drug addiction - Dongming Jia; Dongming Jia; Yuming Xu (Frontiers Media S.A., 2022)
BackgroundPrior studies have consistently revealed that a combination of physical activity with caloric restriction results in a reduction in body weight in the general population. Both overweight and drug abuse are risk factors for poor physiological health, and poor mental health has been associated with drug abuse and unhealthy body mass index (BMI). However, the effects of low-carbohydrates diet (LC) combined with mind-body exercise intervention on improving anthropometric characteristics, lipid metabolism, quality of life, and craving among overweight people who struggle with drug addiction have yet to be clarified.MethodsFifty-four eligible male patients were randomly assigned to the control group (CON; n = 18), the Baduanjin intervention group (BA, 60 min × 5 times/week, 8 weeks; n = 18), and the Baduanjin combined with LC intervention group (LC; n = 18). We compared the anthropometric characteristics, blood biochemical parameters, quality of life, and drug craving responses between the three groups at baseline (week 0), week 4, and week 8.ResultsAfter repeated measurements in the general linear model, both the BA and LC groups exerted significant effects on decreasing waist circumference, BMI, body weight, hip circumference, body fat percentage, total cholesterol level, and triglyceride level (P < 0.05). There was no significant difference in the HDL-C level observed among the BA and LC groups at 8 weeks (P > 0.05); however, there was an overall upwards trend. A significant change in trends in the quality of life scale score was determined in the three groups (P < 0.001). The three groups showed reductions in visual analog scale score distribution over time (P < 0.05).ConclusionsEither Baduanjin or an 8-week Baduanjin combined with LC can significantly reduce anthropometric characteristics and body composition, enhance the quality of life, and reduce craving in overweight/obese patients. Baduanjin combined with LC is particularly effective in improving lipid metabolism.